Solvatochromism of N-aryl-phenylacetamides - Suzana Lj. Apostolov; Jovana Nikolić; Aleksandar D. Marinković (Zaštita Materijala)
Amide derivates are biologically active compounds and they are widely used in all spheres of life. Therefore, it is very important to know their physical-chemical properties. In this work the influence of characteristics and nature of the solvent on the absorption spectra of N-aryl-phenylacetamide was investigated, in order to obtain information about their solvatochromic properties. The spectra of the compounds were recorded in 15 solvents, with different properties, in the wavelength range from 200 to 400 nm. The effect of the solvents on the absorption spectra of N-aryl-phenylacetamide was analyzed by using Kamlet-Taft's solvatochromic model. Also, in order to obtain detailed information on the type and dominance of the interactions that occur between the compound and the surrounding medium, correlations were made with absorption maxima and Hansen's solvent parameters. In addition to the effect of solvent, the impact of the chemical structure on the spectral behavior of tested amide derivatives was analyzed.